OUTDOOR EXPERIENTIAL METHOD FOR ENHANCING STUDENTS' VOCABULARY - Nurul Fadhilah Gazali (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The purpose of this study was to examine the relationship between students' interest in learning through outdoor activity and their vocabulary mastery, as well as whether or not the use of outdoor experiential methods can improve students' vocabulary mastery and whether or not the students are interested in learning vocabulary in this way. This study used quantitative methods, specifically in the form of a quasi-experimental design, to address the aims. Thirty second-graders from Class VIII A served as the experimental group in this study, which was conducted at SMP Darul Aman in March 2020. Thirty second-graders from Class VIII B served as the control group. The researcher administered questionnaires to students to gauge their interest in the outdoor experiential technique and conducted vocabulary tests for the pretest and posttest to get information about the students' progress in vocabulary mastering. Three conclusions come from this study: 1) The students were interested in using the outdoor experiential method to learn vocabulary, 2) the students' interest in the method was positively correlated with their vocabulary mastery, and 3) the outdoor experiential method proved effective in improving students' vocabulary mastery.